Simultaneous Method Development and Validation for Assay of Atorvstatin Calcium and Ezetimibe Drugs in Solid Dosage Form by RP HPLC - Rizwan, Khan M (International Journal of Pharmaceutical & Biological Archive, 2013)
Simultaneous Method Development and Validation for Assay of Atorvstatin Calcium and Ezetimibe Drugs in Solid Dosage Form by RP HPLC